Revision of Neotropical aphrophorine spittlebugs, part 1: Ptyelini (Hemiptera, Cercopoidea) - Hamilton, K. G. Andrew (Zootaxa, 2012)
Cephisus Stål, formerly with only 3 recognized species, is now known from at least 10 species ranging from southwestern USA to Argentina. Eight are keyed and described, including C. siccifolia (Walker), the economic species in South America, C. variolosus (Walker), the common species in Central America, C. brevipennis sp. nov. and C. laticeps sp. nov. from Mexico, plus C. magnificus sp. nov. from Brazil; two other biological species were identified in the C. variolosus species complex from the results of genetic “barcoding.” These are differentiated from Plinthacrus phaleratus, P. mexicanus and P. irroratus (all described by Spinola in 1850) that are new synonyms of Novaphrophara tasmaniae Lallemand, 1940 (as N. phalerata comb. nov.), a species collected recently only in Madagascar. These two genera along with 6 others are placed in the redefined tribe Ptyelini (= Takagiinae syn. nov.) as sister-genus to the palaearctic genus Cnemidanomia Kusnezov (=Takagia Matsumura), suggesting a pre-Oligocene dispersal from the old world to the new. A preliminary key is provided to the families and tribes of Cercopoidea represented in the new world.